An early Myc‐dependent transcriptional program orchestrates cell growth during B‐cell activation. (23rd July 2019) - Tesi, Alessandra; de Pretis, Stefano; Furlan, Mattia; Filipuzzi, Marco; Morelli, Marco J; Andronache, Adrian; Doni, Mirko; Verrecchia, Alessandro; Pelizzola, Mattia; Amati, Bruno; Sabò, Arianna
Abstract: Upon activation, lymphocytes exit quiescence and undergo substantial increases in cell size, accompanied by activation of energy‐producing and anabolic pathways, widespread chromatin decompaction, and elevated transcriptional activity. These changes depend upon prior induction of the Myc transcription factor, but how Myc controls them remains unclear. We addressed this issue by profiling the response to LPS stimulation in wild‐type and c ‐ myc ‐deleted primary mouse B‐cells. Myc is rapidly induced, becomes detectable on virtually all active promoters and enhancers, but has no direct impact on global transcriptional activity. Instead, Myc contributes to the swift up‐ and down‐regulation of several hundred genes, including many known regulators of the aforementioned cellular processes. Myc‐activated promoters are enriched for E‐box consensus motifs, bind Myc at the highest levels, and show enhanced RNA Polymerase II recruitment, the opposite being true at down‐regulated loci. Remarkably, the Myc‐dependent signature identified in activated B‐cells is also enriched in Myc‐driven B‐cell lymphomas: hence, besides modulation of new cancer‐specific programs, the oncogenic action of Myc may largely rely on sustained deregulation of its normal physiological targets. Synopsis: In primary mouse B‐cells, Myc is immediately induced upon mitogenic stimulation and is required for the early regulation of a select, yet complex, set of genes, which mediate subsequent changes in cell physiology. Myc is required for the transcriptional regulation of several hundred genes upon B‐cell activation. Myc‐dependent genes mainly encode proteins involved in biosynthetic processes and cell growth. Myc‐activated genes are characterized by the highest increase in Myc binding to the promoter ("Myc share") and by increased recruitment of RNA polymerase II. Abstract : In primary mouse B‐cells, Myc is immediately induced upon mitogenic stimulation and is required for the early regulation of a select, yet complex, set of genes, which mediate subsequent changes in cell physiology.